Invisible Rankings: When Do Consumers Assume Best-to-Worst Ordinality When Choosing from an Unnumbered List? - Isaac, Mathew S; Mormann, Milica; Pratap Jain, Shailendra (Journal of Consumer Research, 2026)
Abstract Consumers frequently use lists that were created by marketers, experts, or media platforms, such as a list of favorite restaurants. The authors refer to such lists as curated lists because they include items that appear to be endorsed or recommended by the list maker. Although these lists are typically ranked and numbered, marketers sometimes create lists that are not numbered, making it unclear whether the items have been ranked. Twelve studies (N = 5,530) reveal that when presented with an unnumbered curated list, consumers regularly assume that a fundamental characteristic of numbered lists—best-to-worst ordinality—applies. Specifically, the authors find that when a list contains an endorsement cue (e.g., superlative adjectives, markers of exclusivity, list qualification criteria), consumers rely on the conversational norm of best-to-worst ordinality. This inferential process leads consumers to prefer and choose items that are located vertically higher on the list. However, consumers are less likely to assume best-to-worst ordinality when an unnumbered list does not resemble a typical list: when endorsement cues are absent or conversational norms governing lists are weakened in other ways. This research advances knowledge of how consumers process curated lists in everyday consumption contexts, while also providing actionable recommendations for list makers.